Crown square microstrip fractal antenna for wireless application / Amira Putri Mohammad - Mohammad, Amira Putri (2011)
This paper presents the design of a crown square fractal antenna (CSFA) for wireless applications. This CSFA was fabricated on FR4 substrate with dielectric constant of er = 4.7 and thickness, h = 1.6 mm. All the design and simulation was carried out by using a commercial electromagnetic simulator, CST Microwave Studio. Measurements of the parameter of this antenna was carried out by using Vector Network Analyzer (VNA). This work consists of two measurement result that is without and with stub matching. The result for return loss of CSFA without using stub matching for simulation and measurement result are -11.174 dB and -6.091 dB respectively at resonance frequency 5.8 GHz . The simulated and measured results for VSWR are 1.396 dB and 2.968 respectively. All the measurement result without stub matching indicates poor performance and did not meet the specification of the CSFA. The simulation and measurement result by using stub matching, give a better performance and meet all the specification of CSFA. The value of return loss for simulated result at frequency 5.8 GHz is -15.64 dB while for the measured return loss is -11.174 dB. The value of the return loss met the specification of CSFA because both values are lower than -10 dB and indicate good matching. At the centre of frequenc , the value of VSWR for the simulated is 1.396 while measured VSWR is 1.763. Both values were less than 2 which means the design was approximately ideal. It was observed that, both the measured and simulated values of all parameters by using stub matching were close with each other and compact size antenna was realized. The performance of CSFA has been improved.